Policy Evaluation of Cianjur Regional Middle Term Development Plan, 2011-2016: (Study: Road Development Based on South Cianjur Tourism) - Denny Aditya Dwiwarman; M. Didi Turmudzi; Thomas Bustomi (Pasundan Social Science Development, 2020)
This research was initiated by indicating that the policy evaluation of the Regional Development Plan of Cianjur (RPJMD) 2011-2016 has not been optimal yet, primarily related to South Cianjur-based road infrastructure development. The strengthening of the phenomenon has implications on the low purchasing power of society and the low level of public welfare, especially in South Cianjur. Therefore, the researcher focuses on evaluating the Medium-Term Development Plan (RPJMD) of Cianjur regency for 2011-2016 and the Strategy of RPJMD Cianjur policy evaluation is expected to increase people's purchasing power in Cianjur regency. The purpose of the study, among others; first, describe and analyze the evaluation of the Cianjur District Medium-Term Development Plan (RPJMD) policy for 2011-2016, and secondly, to analyze and find the concept of RPJMD policy evaluation strategy that can be done to develop the development of tourism-based road infrastructure, especially in South Cianjur. While the research method using descriptive and research approach using mixed methods, through concurrent embedded design model (mixture is not balanced). The results reveal that the success of RPJMD policy evaluation is empirically determined by dimensions or aspects of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. On the other hand, researchers found another concept or dimension, in addition to the six parameters put forward by Willian N. Dunn (1981). The concept or dimension that researchers find is the dimension of the perception equation. These findings are academically novelty generated in this dissertation. In addition, the study also found that optimizing the RPJMD policy evaluation required a strategy for the Cianjur District Government. The strategy that the Government of Cianjur Regency can do refers to the pattern of priority scale based on the calculation result of Analytical Hierarchy Process (AHP), which essentially follow the pattern; (1) dimension of perception equation, (2) dimension of accuracy, (3) dimension of equalization, (4) dimension of responsiveness. (5) sufficiency dimension, (6) efficiency dimension, (7) effectiveness dimension. This research concludes that policy evaluation of RPJMD Cianjur Regency Year 2011-2016, primarily related to the development of road-based tourism infrastructure empirically has not run optimally, so that implication on society prosperity, especially people residing in South Cianjur Area